BRAND IMAGE, EDUCATIONAL COST, AND FACILITY ON STUDENT SATISFACTION AND LOYALTY AT STIE PELITA INDONESIA PEKANBARU - Ikhwanul Arif; Dadi Komardi; Rizaldi Putra (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This study aims to analyze the influence of brand image, educational cost, and facility on student satisfaction and loyalty at Pelita Indonesia School of Economic Sciences in Pekanbaru. This study was conducted using a quantitative approach. This study took a sample of 183 respondents at Pelita Indonesia School of Economic Sciences in Pekanbaru. The sampling technique was done using proportionate stratified sampling. The data were analyzed using Structural Equation Modeling with AMOS Version 21. The results showed that brand image had a positive and significant influence on student satisfaction. Educational cost had a positive and significant influence on student satisfaction. Facility had a positive and significant influence on student satisfaction. Brand image had a positive and significant influence on student loyalty. Educational cost had a positive and significant influence on student loyalty. Facility did not have a significant influence on student loyalty. Student satisfaction had a positive and significant influence on student loyalty.